A conceptual overview of the relationship between tourism and peace in terms of international relations theories. Issue 5 (4th March 2023) - Çokişler, Dilek Elvan; Çokişler, Nazım
ABSTRACT: The general claim that tourism is a promoter of peace has not been a common topic of study in the discipline of International Relations. The purpose of this article is to provide a conceptual overview, based on International Relations theories, concerning whether peace between societies can be attained by means of tourism. To that end, the study evaluates tourism's potential to promote peace via four theories, namely, neorealism, neoliberalism, constructivism, and the critical theory. According to the findings of the overview, the claim that tourism promotes peace theoretically agrees with the arguments of constructivism and neoliberalism.